(untitled) (The Pakistan Development Review, 1966)
An understanding of the social and psychological forces effecting the use that people make of existing medical care and health facilities is essential to programme planning and administration. Yet, little is known about these forces as they operate in Pakistan and elsewhere with regard to the utilization of such specialized facilities or services as family planning clinics. This analysis of clinic records from the Karachi Family Planning Association (FPA)1 explores certain social forces in clinic utilization in terms of their geographical distribution in this urban area of Pakistan. In the last section of this paper we generalize the term "clinic" to include the wide variety of sources or centres of contraceptive supply provided in the Third Five Year Plan (such as village volunteers, dais1, and shopkeepers) and consider the implications of our findings in terms of this broader concept of clinic. One of the dilemmas faced by administrators of certain clinic-centred public health and family planning programmes is whether to place their clinics within or very near the residential area of the people for whom the service is mainly intended, or to place the clinic somewhat more distant from this primary target group. The main argument for proximity is that most potential clients or patients will not avail themselves of clinic services unless the services or facilities are